ARF6‐Rac1 signaling‐mediated neurite outgrowth is potentiated by the neuronal adaptor FE65 through orchestrating ARF6 and ELMO1. Issue 12 (13th October 2020) - Chan, Wai Wa Ray; Li, Wen; Chang, Raymond Chuen Chung; Lau, Kwok‐Fai
Abstract: Ras‐related C3 botulinum toxin substrate 1 (Rac1) is a member of the Rho family of GTPases that functions as a molecular switch to regulate many important cellular events including actin cytoskeleton remodeling during neurite outgrowth. Engulfment and cell motility 1 (ELMO1)‐dedicator of cytokinesis 1 (DOCK180) is a bipartite guanine nucleotide exchange factor (GEF) complex that has been reported to activate Rac1 on the plasma membrane (PM). Emerging evidence suggests that the small GTPase ADP ribosylation factor 6 (ARF6) activates Rac1 via the ELMO1/DOCK180 complex. However, the exact mechanism by which ARF6 triggers ELMO1/DOCK180‐mediated Rac1 signaling remains unclear. Here, we report that the neuronal scaffold protein FE65 serves as a functional link between ARF6 and ELMO1, allowing the formation of a multimeric signaling complex. Interfering with formation of this complex by transfecting either FE65‐binding‐defective mutants or FE65 siRNA attenuates both ARF6‐ELMO1‐mediated Rac1 activation and neurite elongation. Notably, the PM trafficking of ELMO1 is markedly decreased in cells with suppressed expression of either FE65 or ARF6. Likewise, this process is attenuated in the FE65‐binding‐defective mutants transfected cells. Moreover, overexpression of FE65 increases the amount of ELMO1 in the recycling endosome, an organelle responsible for returning proteins to the PM, whereas knockout of FE65 shows opposite effect. Together, our data indicates that FE65 potentiates ARF6‐Rac1 signaling by orchestrating ARF6 and ELMO1 to promote the PM trafficking of ELMO1 via the endosomal recycling pathway, and thus, promotes Rac1‐mediated neurite outgrowth.